Association of the chronic kidney disease urinary proteomic predictor CKD273 with clinical risk factors of graft failure in kidney allograft recipients. Issue 10 (11th October 2021) - Rambabova-Bushljetik, Irena; Metzger, Jochen; Siwy, Justyna; Dohcev, Saso; Bushljetikj, Oliver; Filipce, Venko; Trajceska, Lada; Mischak, Harald; Spasovski, Goce
ABSTRACT: Background: Kidney transplantation is the best treatment option for end-stage kidney disease but is still associated with long-term graft failure. In this study, we evaluated the application of urinary proteomics to identify grafts with high failure risk before initial decline of estimated glomerular filtration rate (eGFR) with irreversible graft changes. Methods: Fifty-two living donor kidney transplant recipients (KTR) with 8-year follow-up were enrolled. All patients underwent clinical examination and had a routine laboratory screening at 3, 6, 12, 24, 36, 48 and 96 months post-transplantation, including creatinine, urea, albumin and 24-h proteinuria. Graft function was estimated according to Nankivell. Urine samples at Month 24 were analysed by capillary electrophoresis coupled mass spectrometry followed by classification with the chronic kidney disease classifier CKD273. Results: CKD273 showed significant correlation with serum creatinine at every time point and moderate inverse correlation for the slope in glomerular filtration rates by Nankivell ( r = −0.29, P = 0.05). Receiver operating characteristics analysis for graft loss and death within the next 6 years after proteomic analysis resulted in an area under curve value of 0.89 for CKD273 being superior to 0.67 for Nankivell eGFR. Stratification into CKD273-positive and -negative patient groups revealed a hazard ratio of 16.5 for prevalence of graft loss in case of CKD273 positivity. Conclusions: Using a representative KTR cohort with 8-year follow-up, we could demonstrate significant value of CKD273 for risk stratification of graft loss. This study provides the conceptual basis for further evaluation of CKD273 as a prognostic tool for long-term graft function risk stratification by large prospective clinical trials. Graphical Abstract: